PERAN EKONOMI KREATIF DALAM MENINGKATKAN PENDAPATAN LEMBAGA PERS MAHASISWA INKADHA SUMENEP DITINJAU DARI BISNIS ISLAM - Utami, Kristiani; Sayyidi (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2023)
Research Journal with the title "The Role of Creative Economics in Increasing the Income of Student Press Institution Inkadha Sumenep Reviewed from Islamic Business" In the view of Islamic economics Regarding the income obtained from the results of business carried out by student members of the LPM (Student Press Institute) on the Inkadha Campus Sumenep. The field research we are currently using is descriptive qualitative research, namely research carried out to find facts in the field or actual facts, then the data is processed and described to determine the impact or results on improving the economy of students who are members of the LPM (Student Press Institute) at Inkadha Sumenep. Data collection in this research used interview techniques, and was supported by observation and documentation. The data analysis techniques used, according to Miles and Huberman, include: data reduction, data presentation and drawing conclusions and verification. Meanwhile, the technique of checking the validity of the data used in this research journal is carried out by extending observations, increasing persistence in research, triangulation, and discussions with colleagues. The results of this research are: 1) Student members of the LPM (Student Press Institute) who are directly involved in the business they are currently pursuing have a positive impact on increasing their income which improves their standard of living or economy. 2) The second is that it indirectly increases work experience and insight for student members of the Inkadha Sumenep Press. 3) In connection with this research, the performance or service to consumers provided by employees or student members of the Press has fulfilled the rules or perspectives in business Islam. A business that produces benefits and is not prohibited by religion, from various good stages so that the results or wages obtained from the business are declared legal or halal and are not a problem.